تطوير المواد التعليمية للقراءة باستخدام بادليت لتنمية كفائة التلاميذ في تعلم اللغة العربية في المدرسة الثانوية الإسلامية الحكومية الأولى روكن هولو - Agustar Agustar; Masrun Masrun; Agustiar Agustiar; Hakmi Wahyudi (At-Tajdid : Journal of Islamic Studies, 2021)
The study aims at depeloving and producing material products to teach Arabic reading skills by using media padlet to know the worth of teaching materials for reading skills using padlet media, and to learn to the extent of the effectiveness of teaching materials with medium padlet to improve Arabic reading skills of state Islamic Senior High School I Rokan Hulu. The methods used in this study are research and development methods (R&D) with qualitative and quantative approaches. In the depelovment, with depelovment steps of : analliysis, design, depelovment, implementation, and evaluation. The data- gathering technique USES analysis for content, descriptive analysis and descriptive statistical analysis. The result of study is : 1) in developing materials speak with the Padlet approach, researchers do needs analysis by interviews with teacher and students need, design products, develop products using Padlet media, test products in students too see the effectiveness of the product, then evaluate each development. 2) Product worth test on materials 85%, linguistics 86%, and design specialist 95%, with a “ excellent” category. 3) effectiveness through tests of t with a degree of 0.05 achieves result to hasil t0 > 3,300 tt 1, 753 = 5% meaning ha received and Ho rejected. And so there is a significant difference. It may be concluded that reading material with medium Padlet is effective and interesting for use.